CFD-моделювання теплоаеродинамічних характеристик поверхні з гвинтоподібних труб - Рогачов, Валерій Андрійович; Терех, Олександр Михайлович; Баранюк, Олександр Володимирович (НТУ "ХПІ", 2018)
Засобами CFD-моделювання досліджений конвективний теплообмін та аеродинамічний опір шахових пучків гвинтоподібних труб з рівнорозвиненою поверхнею в діапазоні зміни чисел Рейнольдса від 9,5∙103 до 45∙103. Вивчені моделі пучків з відношеннями кроків між трубами s1/s2 = 0,46, 0,92 і 1,83. Пучки формувались з трьох досліджених типів однозахідних гвинтоподібних труб, які відрізнялися кроком гвинтової лінії – t = 8, 12 i 20 мм. Зовнішній діаметр D = 16 мм, глибина виступів-впадин h = 2,5 мм і загальна довжина l = 428 мм досліджених труб не змінювались. Запропоновані залежності для розрахунку конвективних коефіцієнтів тепловіддачі і аеродинамічного опору шахових пучків гвинтоподібних труб. Приведений теплоаеродинамічний розрахунок повітронагрівача-регенератора.

Using CFD-simulation tools we studied the convection heat exchange and the aerodynamic characteristics of the staggered bundles of helical tubes with the isotomous surface exposed to the external air flow stream in the range of Reynolds numbers of 9,5∙103 to 45∙103. Bundle models with the relation of pitches between the tubes of s1/s2 = 0.46, 0.92 and 1.83 have been studied. The bundles were formed of three studied types of single thread helical tubes with the helical line pitch of t = 8, 12 and 20 mm. The outer tube diameter of D = 16 mm, the projectioncavity depth of h = 2,5 mm and the total length of l = 428 mm of test tubes were unvaried. CFD simulation of the stream and heat exchange is based on the construction of the geometric model of calculated area and its discretization according to the conception of influence of the network parameters of finite elements on the stability and convergence of the solution and the specification of boundary conditions. The calculated area is covered with the nonuniform tetrahedral network concentrating near the tube walls. A minimum pitch size near the tube wall is selected provided that Re–1. Minimum and maximum pitches are in this case 5∙10–5 and 1∙10–4 m. A number of the cells required for the flow discretization in the intertubular space was within 4 million. Model computations were done for periodic boundary conditions that were defined in profile planes at a distance between them equal to the transverse pitch s1. The process was analyzed using the developed finite element CFD-models of helical tubes in the ABSYS-Fluent program system environment. The formulated problem was solved for the stationary problem description meeting the requirement of achieving the independence of the solution on calculation network compactness. The obtained research data allowed us to suggest power dependences to compute the convective coefficients of heat emission and the aerodynamic resistance of staggered bundles of helical tubes. The tubes with the helical line pitch of t = 20 mm have the highest heat exchange intensity and the tubes with t = 8 mm have the lowest heat exchange intensity. In comparison with smooth tubular bundles, the highest increase in the heat emission (19–24 %) is observed for the bundles of helical tubes with t = 20 mm (t/h = 8), and the lowest increase (10–16 %) is observed for the bundles with t = 8 mm (t/h = 3.2). It is shown, that the resistance of the bundle of helical tubes with s1/s2 = 0.46 is higher by 17 % and 20 % in comparison with the bundles of s1/s2 = 0.92 and 1.83, accordingly. All studied bundles of helical tubes have a higher aerodynamic resistance in comparison with smooth tubular bundles with the same geometric parameters. Thus, the resistance of the bundle of helical tubes with з s1/s2 = 1.83 is higher by 46 % and that of the tube bundle with s1/s2 = 0.46 and s1/s2 = 0.92 is higher by 14 % and 5 %, accordingly. The design heat aerodynamic computation data are given for the air-heater-regenerator that consists of the sections of heat-exchange surfaces of the helical tubes. The computation was done using the standard method involving the proposed dependences. It was shown that the heat exchanger made up of helical tubes has lower overall dimensions in comparison with smooth tubular heat exchanger and its heat transfer coefficient is 1.7 times higher.
CFD-simulation of heat aerodynamic characteristics of the surface of helical tubes
Keywords: пучок шаховий; теплообмін; опір аеродинамічний; staggered bundles; heat exchange; aerodynamic resistance; generalizing dependence